Anti Bullying Berorientasi Kewirausahaan sebagai Upaya Pencegahan Perundungan di Lingkungan Madrasah - Mukhlis; Sirajuddin; Dina, Dina Amalia; Fatima Azzahra; Witasari (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
Bullying remains a crtitical threat to the educational ecosystem in madrasah ibtidai’iyah (elementary Islamic school), where students aged 7-12 are vulnerable to aggression that hinders their character development. This community service activity implemented an entrepreneurship -oriented anti-bullying workshop by PKM team from primary education, Universitas Muhammadiyah Makassar, to prevent harassment through teacher-student collaboration in producing simple products featuring motivational anti-bullying messages on packaging. The workshop was conducted on Desember 2025, at MI DDI Mangempang, Maros Regency, Involving 27 teachers and students in 5 heterogeneous groups, using recycled materials (cardboard, markers, fabric scraps). All group produced 5 product prototypes, this approach fosters community aggression into creative entrepreneurship, offering a novel, sustainable prevantion.